Amerindian Livelihoods, Outside Interventions, and Poverty Traps in the Ecuadorian Amazon1. (11th April 2013) - Rudel, Thomas K.; Katan, Tuntiak; Horowitz, Bruce
Abstract Recent efforts to explain the persistence of rural poverty have made frequent use of the concept of poverty traps, understood as self‐reinforcing poverty. The dynamic dimension of the poverty trap concept makes it a potentially useful tool for understanding conditions of persistent poverty, especially in circumstances where outside interventions "shock" the system with the intention of ending poverty and disadvantage. This article describes one such effort among a populous group of lowland Amerindians, the Shuar of Ecuador's Amazon region. Three small household surveys conducted at different times during the last 25 years suggest that the Shuar, despite having obtained access to land through a combination of their own efforts and outside interventions, have become enmeshed in a natural‐resource‐degrading poverty trap. Mestizos with land in the same region avoided this trap only by emigrating in large numbers. Secure access to land did not prevent the emergence of a poverty trap among the Shuar in large part because smallholders in Latin America faced difficult macrosociological and ecological conditions during the last decades of the twentieth century.